Patient-specific choice of an antiplatelet drug for long-term therapy of coronary heart disease: rationale and implementationL - NA Mazur (Медицинский совет, 2014)
In all urbanized countries, more than half of overall mortality is conditioned by diseases caused by atherothrombosis in the arteries of heart and brain. In Russia, as compared with Europe and the United States, the mortality rate is 3-5 times higher. The key factors that in many countries contributed to a reduction in mortality over the past 15-20 years, in addition to overall popularization of a healthy lifestyle and healthy diet, was the widespread use of antiplatelets for the prevention and treatment of atherothrombotic events in high-risk groups. However, in populations with low risks of coronary artery disease and brain ischemia, aspirin therapy did not result in a decrease in cardiovascular mortality, which was confirmed by a follow-up of 95,000 patients at low risk for an average period of 6.9 years. [1]